2014
DOI: 10.3329/bmj.v43i2.21391
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of acid burn victims in two selected health facilities in Dhaka city

Abstract: Abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 0 publications
1
6
0
Order By: Relevance
“…Islam et al () revealed 84% ( N = 112) faced psychological problems following the attack, in agreement with Lama et al's () study, where 8% ( N = 36) had a psychological condition and 53% reported interpersonal conflict or adjustment problems. Thus, rehabilitative support is necessary.…”
Section: Resultssupporting
confidence: 76%
See 3 more Smart Citations
“…Islam et al () revealed 84% ( N = 112) faced psychological problems following the attack, in agreement with Lama et al's () study, where 8% ( N = 36) had a psychological condition and 53% reported interpersonal conflict or adjustment problems. Thus, rehabilitative support is necessary.…”
Section: Resultssupporting
confidence: 76%
“…Some survivors experienced anger, increased annoyance, and loss of temper; adding strain on family relations. Other studies found that 50% (N = 36) survivors lacked family support and 84% (N = 112) experienced family negligence and dependence for day-to-day living (Islam et al, 2014;Lama et al, 2015). Consequently, the pre-morbid functioning of the family unit in society changed, creating additional burdens and leaving some without a support system.…”
Section: Impact On Familymentioning
confidence: 99%
See 2 more Smart Citations
“…Family conflict, marriage proposal rejection and financial matters are the examples that have been mentioned in this study to be cause of "accidental" burns. Such examples have been stated to be intentional and not accidental, since a motive or an "intention" is involved in such kind or cause of burn [4,5]. Knowing the cause or kind whether intentional or accidental becomes important as the cause of any underlying stress or depression or lack of self-esteem can be better evaluated, and an insight is provided if the event of burn has aggravated such mental state of depression or lack of self-esteem.…”
mentioning
confidence: 99%